(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Mental health indicates the degree of mental prosperity. When a person faces an unbalanced mental health, it effects in intellectual disorder. In India, the number of cases regarding the mental sickness is growing every year, and there’s a shortage in the intellectual healthcare experts, additionally nonetheless taken into consideration as taboo. In such conditions, technologies like Artificial Intelligence allows to fill the space. As Artificial intelligence is dedicated to developing structures that carry out cognitive methods characteristics of human beings, we will use this in mental fitness associated troubles. As we are going thru a difficult time of COVID-19 wherein everything has been online, why not use this opportunity to help humans on-line. Chatbots are predicted to upward thrust in recognition because the demand for intellectual health treatment grows in tandem with technological advancements. While an AI chatbot can provide a person with equipment and a platform to cope with problems, as well as a mechanism to music moods and enhance intellectual fitness literacy, it isn’t an alternative choice to a therapist or different intellectual fitness company. Finally, if AI chatbots have a high quality impact on intellectual health, they should be regulated, and society have to resist techno-fundamentalism in relation to AI. Many companies have recently begun to use chatbots to answer user questions through chat interfaces. Although it has end up easier to construct a chatbot application thanks to latest technological improvements, the application itself is complex device. While designing a chatbot, its miles tough to reap efficiency, efficacy, and person delight. Chatbots have usurped the role of humans due to their recognition and user-friendly capabilities.